2020
DOI: 10.1039/d0ra05108j
|View full text |Cite
|
Sign up to set email alerts
|

PDMPO: a specific silicon or silica, pH sensitive fluorescent probe?

Abstract: To understand Si behavior in soils and plants, we evaluated the use of PDMPO that was supposed to be a Si-specific, pH-dependent fluorescence marker. We found that the PDMPO fluorescence is neither Si-specific nor pH dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The tested Cu 2+ concentrations were 10 -9 , 10 -6 , 4 10 -6 , 10 -5 , 4 10 -5 , 10 -4 , 4 10 -4 , 10 -3 and 4 10 -3 mol L -1 , the highest concentrations being low enough to avoid precipitation of Cu(OH)2 at the working pH. As the fluorescence intensity of humic substances is highly sensitive to pH [21], the pH of the solutions was adjusted to pH 5.3 using NaOH and HCl solutions, that were preferred to usual buffers in order to avoid any impact on the fluorescence signal [22]. The ionic strength (I) was adjusted to 0.01, 0.1 and 0.5 mol L -1 using NaCl.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The tested Cu 2+ concentrations were 10 -9 , 10 -6 , 4 10 -6 , 10 -5 , 4 10 -5 , 10 -4 , 4 10 -4 , 10 -3 and 4 10 -3 mol L -1 , the highest concentrations being low enough to avoid precipitation of Cu(OH)2 at the working pH. As the fluorescence intensity of humic substances is highly sensitive to pH [21], the pH of the solutions was adjusted to pH 5.3 using NaOH and HCl solutions, that were preferred to usual buffers in order to avoid any impact on the fluorescence signal [22]. The ionic strength (I) was adjusted to 0.01, 0.1 and 0.5 mol L -1 using NaCl.…”
Section: Sample Preparationmentioning
confidence: 99%
“…We recorded the fluorescence intensity of the HA fluorophore that had the higher intensity without an added compound as a function of Si, Al or both together at three pH (4, 7 and 9) adjusted with HCl and NaOH, which were preferred over the usual buffers in order to avoid any impact on the fluorescence signal (Merdy et al, 2020). During the fluorescence quenching experiment, it checks should be made for the absence of solid precipitation after each addition of Si or Al.…”
Section: Fluorescence Quenching or Enhancementmentioning
confidence: 99%
“…Metal ions or other complexing molecules are able to quench the fluorescence of organic ligands when they complex to these functional groups(Gauthier et al, 1986; Elkins and Donald, 2002; Provenzano et al, 2004). They can, in some cases, enhance the fluorescence intensity(Merdy et al, 2020 ;Manoharan et al, 2014).…”
mentioning
confidence: 99%
“…26 We have previously shown that when bound to silica, PDMPO resides within the Stern layer which affects the dye's excited state behaviour and chromaticity. 27 While recent work has challenged the view that PMDPO has a unique Si specific fluorescence based on solution studies, 28 the behaviour of PMDPO on the surface of solid phase silica remains a useful probe. Here, we demonstrate a new surface charge imaging method using the relationship between zeta ( ζ ) potential, feature size of nanoparticles, and PDMPO fluorescence.…”
Section: Introductionmentioning
confidence: 99%